2019
DOI: 10.2478/hukin-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between the Expression of the ACTN3 Gene and Explosive Power of Soccer Players

Abstract: Muscle strength and maximal speed are factors determining athlete’s results during competition. Their association with ACTN3 gene activity has been documented. The purpose of this study was the analysis of ACTN3 gene expression during a 2 month training cycle of soccer players and its correlation with the countermovement jump (CMJ) and squat jump (SJ). The study group consisted of 22 soccer players (aged 17‐18). The study material included peripheral blood lymphocytes. The relative expression (RQ) of the ACTN3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…The presence of the RR genotype of this polymorphism is associated with the full expression of the alpha-actinin-3 protein in fast-twitch muscle fibers, a crucial feature for long-duration and high-intensity activities like mountain ultramarathons [ 31 ]. The correlation with BMI may suggest that athletes with this genotype, who tend to have greater muscle mass, can more effectively handle the demands of mountain running, where muscular strength and endurance are vital [ 14 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the RR genotype of this polymorphism is associated with the full expression of the alpha-actinin-3 protein in fast-twitch muscle fibers, a crucial feature for long-duration and high-intensity activities like mountain ultramarathons [ 31 ]. The correlation with BMI may suggest that athletes with this genotype, who tend to have greater muscle mass, can more effectively handle the demands of mountain running, where muscular strength and endurance are vital [ 14 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that both male and female elite sprinters have significantly higher frequencies of the 577R allele compared to controls. Since then, ACTN3 R577X has been studied in other cohorts such as rowers [ 132 ], soccer players [ 133 ], ironman triathletes [ 134 ], basketball [ 135 ] etc. Some articles have reported a strong association between the RR genotype and elite power performance [ 136 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pese a que la relación entre somatotipo y genotipo en deportistas de elite ha sido bien descrita en la literatura por diferentes autores (Domanska-Senderowska et al, 2019;Potocka et al, 2019), esta no fue posible comprobarla en este estudio. Esto pudiera deberse a que la variación de somatotipo depende en gran medida de la carga y tipo de entrenamiento, factor fundamental a la hora de separar el deporte de competición del deporte de alto rendimiento.…”
Section: Discussionunclassified